Familial TAB2 microdeletion and congenital heart defects including unusual valve dysplasia and tetralogy of fallot. (2nd July 2015) - Weiss, Karin; Applegate, Carolyn; Wang, Tao; Batista, Denise A. S.
<x xml:space="preserve">Abstract</x> Haploinsufficiency of TAB2 was recently implicated as a cause for a variety of congenital heart defects. Reported cases have genomic deletions of 2–10 Mbs including TAB2 at 6q24–25 are almost always de novo and show variable cardiac and extra cardiac phenotype. We report on an inherited, 281 kb deletion in a three generation family. This is the smallest reported deletion involving TAB2 that segregates with congenital heart defects. Three affected individuals in this family present with myxomatous cardiac valves in addition to structural heart defects commonly associated with TAB2 deletions. Findings from this family support a key role of TAB2 haploinsufficiency in congenital heart defects and expand the phenotypic spectrum of TAB2‐microdeletion syndrome. © 2015 Wiley Periodicals, Inc.